Simulation of Surfactant-Oil-Solvent Ternary System: Mean Field Theory - AL-SHANNAG, MOHAMMAD; MATOUQ, MOHAMMED; AL-ANBER, ZAID (Asian Journal of Chemistry, 2010)
The properties of ternary mixtures of surfactant-oilwater based on the use of the single chain mean-field (SCMF) theory is presented. A new methodology is applied where the chains of surfactant and oil are thrown randomly onto a threedimensional lattice of size L × L × L. We determine the critical micelle concentrations, density distribution and the cluster size distributions for the H4T4 amphiphile and oil molecules, Tx, of length x in a water solvent. A good agreement of the critical micelle concentration values with those of Monte Carlo simulations is obtained.